Bilingual aphasia and recovery of the affected language - Moreno Agurto, Víctor A. (2019)
The language disorder caused by injury to the central nervous system in a person who speaks two languages iscalled bilingual aphasia, and so that a person can recover one of the languages, several factors influence on it.Thus, while some authors stablish that the mother tongue would be more likely to be rescued, others point out that it would be the one that was used the longest.